2019
DOI: 10.3390/ijerph16214076
|View full text |Cite
|
Sign up to set email alerts
|

Stable H-O Isotopic Composition and Water Quality Assessment of Surface Water and Groundwater: A Case Study in the Dabie Mountains, Central China

Abstract: In order to understand the water cycle and assess the water quality for irrigation purposes in the Upper Pi River Basin (UPRB), which is the northern slope of the Dabie Mountains, 68 surface water and groundwater samples were collected and analyzed for H-O isotopes and hydrochemistry during the high-flow season in 2017 and 2018. The results show that ranges of hydrogen and oxygen isotopic composition (δ2H: −68.8‰ to −40.8‰, δ18O: −10.05‰ to −5.05‰) are controlled by the medium latitude and high altitude of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Hence, Lancang River water did not experience significant evaporation. Scatter plots of δ 18 O and δ 2 H in the wet season in the river water of the Lancang River (this study), the Yellow River [38], the Huai River [30,39], the Yangtze River [40], the Jiulong River [29], the Pearl River [41], and the Mun River [42]. Table 1.…”
Section: H and O Isotopic Compositionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, Lancang River water did not experience significant evaporation. Scatter plots of δ 18 O and δ 2 H in the wet season in the river water of the Lancang River (this study), the Yellow River [38], the Huai River [30,39], the Yangtze River [40], the Jiulong River [29], the Pearl River [41], and the Mun River [42]. Table 1.…”
Section: H and O Isotopic Compositionmentioning
confidence: 99%
“…Locations, water temperature (T), dissolved oxygen (DO), total dissolved solid (TDS), and isotope composition of river water samples. We compared the stable isotopic composition in the wet season of the water of seven rivers in Asia, characterized by different climate types and altitudes, including the Lancang River (this study), the Yellow River, mainly in the temperate zone [38], the Huai River in the temperate-subtropical transition zone [30,39], the Yangtze River, mainly in the subtropical zone [40], the Jiulong River in the subtropical zone [29], the Pearl River in the subtropical zone [41], and the Mun River in the tropical zone [42]. In Figure 2, the mean values of the isotopic composition of different rivers were obviously different, especially when comparing the Lancang River with other rivers.…”
Section: H and O Isotopic Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of water sampling, pre‐treatment, analysis and accuracy have been provided earlier (Dong & Brooks, 2006; Shiller et al, 2006; Zhang et al, 2022). Analyses of major ion (F − , Cl − , NO 3 − , SO 4 2− , HCO 3 − , CO 3 2− , Na + , K + , Mg 2+ and Ca 2+ ), elemental (Li, Be, Sc, Ti, V, Mn, Cr, Co, Ni, Cu, Zn, Ga, Rb, Y, Nb, Mo, Cd, Sb, Cs, Ba, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, W, Tl, Pb, Bi, Th, U, Sr, B) and O–H isotopic compositions (Yang et al, 2019) were undertaken at the Analysis and Testing Center of Beijing Research Institute of Uranium Geology, China.…”
Section: Sampling and Analysismentioning
confidence: 99%
“…Moreover, several studies have found that evaporation and water rock interaction can increase the δ 18 O in the water, then leading to the decrease of d-excess [33,34]. In this study, the d-excess of RW samples ranges from −4.5 to 5.7‰ (mean = −0.2‰), which is lower than the d-excess value of atmospheric precipitation ( Table 1 and Figure 5), and therefore, the river water might have been affected by evaporation.…”
Section: The Evolution Of Hydrogen and Oxygen Isotopesmentioning
confidence: 99%